ChemInform Abstract: Meglumine Catalyzed Expeditious Four‐Component Domino Protocol for Synthesis of Pyrazolopyranopyrimidines in Aqueous Medium. Issue 15 (April 2015) - Li, Xiao‐Tang; Zhao, Ai‐Dong; Mo, Li‐Ping; Zhang, Zhan‐Hui
Abstract: A facile and highly efficient protocol for the one‐pot, four‐component reaction of ethyl acetoacetate, hydrazine hydrate, aromatic aldehydes, and barbituric acid has been developed using meglumine as an inexpensive, biodegradable, and reusable catalyst.